Physical and mental health of 40,000 older women in England during the COVID-19 pandemic (2020–2021) - Floud, S; Hermon, C; Reeves, GK (Public Library of Science, 2024)
Background To assess factors associated with perceived changes in physical and mental health and with delays in seeking healthcare during the second and third COVID-19 lockdowns in England (2020–2021).